In vitro microbicidal, anti‐biofilm and cytotoxic effects of different commercial antiseptics. Issue 3 (10th June 2016) - Ortega‐Peña, Silvestre; Hidalgo‐González, Christian; Robson, Martin C; Krötzsch, Edgar
Abstract: Topical antiseptics are widely used for wound treatment, with the goal of disrupting biofilm capacity. We analysed the effectiveness of a variety of antiseptics to inhibit various stages of biofilm formation and to remove biofilms in vitro as well as the agents' cytotoxic effects on fibroblasts. We found that the chlorine‐releasing agents exhibited immediate anti‐biofilm effects in the short term, with lesser cytotoxicity than agents prepared from more stable compounds, such as biguanide or modified diallyl disulfide‐oxide, which, conversely, have better long‐term effectiveness. Among the examined organisms, Gram‐positive bacteria and Candida albicans were the most sensitive to the antiseptics, whereas Pseudomonas aeruginosa and Acinetobacter baumannii were relatively resistant to them. Formulations whose mechanisms of action involve the release of chemically active chlorine were more effective when administered in solution than the gel form, likely because of the stability of the active ingredients during or after preparation of the formula. Interestingly, hypochlorous acid and some superoxidation solutions were effective in preventing biofilm formation within a short time period and showed virtually no toxicity. Our study indicates that most antiseptics remain effective long enough to prevent biofilm formation; thus, even brief application of an antiseptic agent during initial wound treatment can lead to better wound management outcomes.